Identifying the Challenges and Opportunities of Virtual Teaching During the Coronavirus Pandemic from the Teachers’ Point of View - Hemati Rad, Farzaneh; Khodarahmi, Someyeh; Momeni, Hassan (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study was carried out aiming to identify the challenges and opportunities of virtual teaching during the Coronavirus pandemic from the perspective of teachers.Methodology: The present study was applied in terms of its purpose and qualitative in terms of its implementation. The statistical population includes middle school and high school teachers in the city of Dehloran during the 2020-2021 school year. The sample size was determined 18 people based on the principle of theoretical saturation and purposive sampling was used. The study was conducted through semi-constructed interviews and data analysis was done based on thematic analysis. The credibility of the findings was assessed using face validity (Five academic experts including two sociology professors, one psychology professor, and two curriculum design professors) and Cohen’s kappa agreement coefficient was used for reliability, for which a value of 0.88 was obtained.Findings: Findings show that 23 open codes and 7 axial codes (a globalized approach, parents’ experiences, the lower psychological and economic cost of virtual teaching, the constant nature of virtual teaching, the adaptability of pillars of the education system, a selective teaching method, and teachers’ social status) were identified as opportunities of virtual teaching. Also, 24 open codes and 8 axial codes (infrastructural factors, economic challenges, ambiguity about roles, lack of technological skills, lost motivation in teachers and students, the risk of teaching, and teachers’ competencies) were identified as challenges of virtual education during the pandemic.Conclusion: Given the uncertainty of when the pandemic will be completely done with, the continuation of virtual teaching is necessary and those in charge of education must seriously pay attention to the present challenges to improve its quality.